Type 1 diabetes, glycemic traits, and risk of dental caries: a Mendelian randomization study - Tan, Li; Zhong, Meng-Mei; Zhao, Ya-Qiong; Zhao, Jie; Dusenge, Marie Aimee; Feng, Yao; Ye, Qin; Hu, Jing; Ou-Yang, Ze-Yue; Chen, Ning-Xin; Su, Xiao-Lin; Zhang, Qian; et al. (Frontiers in Genetics, 2023)
Background: Regarding past epidemiological studies, there is disagreement over whether type 1 diabetes (T1DM) is one of the risk factors for dental caries. The purpose of this study was to determine the causative links between genetic susceptibility to T1DM, glycemic traits, and risk of dental caries using Mendelian randomization (MR) approaches.Methods: Summary-level data were collected from genome-wide association studies (GWAS) of T1DM, fasting glucose (FG), glycated hemoglobin (HbA1c), fasting insulin (FI), and dental caries.MR was performed using the inverse-variance weighting (IVW) method, and sensitivity analyses were conducted using the MR-Egger, weighted median, weighted mode, replication cohort, as well as multivariable MR conditioning on potential mediators.The risk of dental caries increased as a result of genetic susceptibility to T1DM (odds ratio, OR = 1.044; 95% confidence interval [CI] = 1.015-1.074; p = 0.003), with consistent findings in replication cohort. The relationship between T1DM and dental caries was stable when adjusted for BMI, smoking, alcohol intake and type 2 diabetes (T2DM) in multivariable MR. However, no significant correlations between the risk of dental caries and FG, HbA1c, or FI were found.These results indicate that T1DM has causal involvement in the genesis of dental caries. Therefore, the periodic reinforcement of oral hygiene instructions needs to be added to the management and early multidisciplinary intervention of T1DM patients, especially among adolescents and teenagers, who are more susceptible to T1DM.